Lithium cobalt oxide positive electrode material and preparation method thereof, positive electrode plate, secondary battery and electric device

By covering the surface of lithium cobalt oxide with a small layer of MXene material and performing high-temperature annealing, the problem of structural instability and shortening of cycle life of lithium cobalt oxide batteries when increasing the charging cutoff voltage is solved, and higher electrochemical performance and safety are achieved.

CN119864382APending Publication Date: 2025-04-22TIANJIN B&M SCI & TECH LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311366092.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

When existing lithium cobalt oxide batteries increase the charging cutoff voltage to increase energy density, problems such as structural instability, delimiting the surface of the material, cobalt dissolution and oxygen deletion lead to a shortening of the cycle life and reducing safety.

Method used

A small layer of MXene material is uniformly coated in situ on the surface of lithium cobalt oxide, and subjected to high-temperature annealing treatment under an inert gas to prepare a lithium cobalt oxide-based positive electrode material with a high-conductive coating.

Benefits of technology

By improving the conductivity and structural stability of the lithium cobalt oxide surface, the ion and electron conduction capabilities of the positive electrode material are enhanced, thereby improving the electrochemical performance and cycle life of the lithium cobalt oxide-based positive electrode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864382A_ABST
    Figure CN119864382A_ABST
Patent Text Reader

Abstract

The invention provides a lithium cobalt oxide type positive electrode material and a preparation method thereof, a positive electrode plate, a secondary battery and an electric device, the lithium cobalt oxide type positive electrode material comprises an inner core and a coating layer coating at least part of the surface of the inner core; the core comprises a lithium cobalt oxide doped with a metallic element or a non-metallic element, the coating layer comprises a few-layer MXene material with a chemical formula of Mn + 1Xn, the element M comprises one or more of Ta, Ti, V, Cr, Zr, Nb and Mo, the element X comprises one or more of C and N, the surface end group of the few-layer MXene material comprises one or more of-O,-OH and-F, and n is a positive integer and is greater than or equal to 1 and less than or equal to 3. The surface of the lithium cobalt oxide is coated with the MXene material, so that the prepared lithium cobalt oxide positive electrode material has excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium cobalt oxide positive electrode material and a preparation method thereof, a positive electrode sheet, a secondary battery and an electrical device. Background Art

[0002] Rechargeable lithium-ion batteries are a new generation of green energy storage batteries, with outstanding advantages such as high energy density, no memory effect, good cycle stability and long service life. They have been widely used in 3C, smart networking, distributed energy storage and other fields. As 3C products are updated more frequently, the development trend of 3C products to be "lighter, thinner and more durable" has put forward higher requirements on the energy density of lithium-ion batteries.

[0003] At present, the energy density of lithium cobalt oxide batteries is mainly improved by increasing the charge cut-off voltage. However, increasing the charge cut-off voltage will cause more lithium ions to escape from the lattice, which will cause structural instability; the degree of lithium removal from the surface of the material will increase, and the structural phase change will extend from the surface of the material to the inside of the particles; high-valent cobalt is unstable and has strong oxidizing properties, which is easy to react with the electrolyte; the dissolution of cobalt is accompanied by the escape of oxygen and the occurrence of gas production. These factors will shorten the cycle life and reduce safety, affecting the practical application of high-voltage lithium cobalt oxide.

[0004] Therefore, the improvement in the related art mainly adopts doping, surface coating, optimization of electrolyte, use of functional diaphragm, etc. However, when coating the surface of lithium cobalt oxide in the related art, although the violent reaction between lithium cobalt oxide and electrolyte can be effectively alleviated, the electrochemical performance of the positive electrode material is also affected. Summary of the invention

[0005] Based on this, it is necessary to provide a lithium cobalt oxide positive electrode material and its preparation method, a positive electrode plate, a secondary battery and an electrical device to facilitate the electrochemical performance of the positive electrode material.

[0006] The first aspect of the present invention provides a lithium cobalt oxide positive electrode material, comprising:

[0007] a core comprising lithium cobalt oxide doped with a metal element or a non-metal element; and

[0008] The coating layer is coated on at least part of the surface of the core, and the coating layer comprises a chemical formula of M n+1 X n A few-layer MXene material, wherein the M element includes one or more of Ta, Ti, V, Cr, Zr, Nb and Mo, the X element includes one or more of C and N, the surface end groups of the few-layer MXene material include one or more of -O, -OH and -F, n is a positive integer, and 1≤n≤3.

[0009] In some embodiments, the chemical formula of the lithium cobalt oxide is Li a Co b M' c O2, wherein 0.97≤a≤1.02, 0.8≤b≤1.02, 0.002≤c≤0.05, and the M' element includes a combination of one or more of Mg, Ti, Ni, Mn, W, Y, Mn, F, Zr, B, Al, V, Zn, Nb and La.

[0010] In some embodiments, the coating layer has a thickness of 5 nm to 30 nm.

[0011] The second aspect of the present invention provides a method for preparing the lithium cobalt oxide positive electrode material of the first aspect of the present invention, comprising the following steps:

[0012] The lithium cobalt oxide is mixed with a solvent, ultrasonicated, and the few-layer MXene material is added to prepare a dispersion;

[0013] The solvent in the dispersion is removed and then a first calcination treatment is performed to prepare the lithium cobalt oxide positive electrode material.

[0014] In some embodiments, the mass ratio of the lithium cobalt oxide to the few-layer MXene material is 10:(0.05-0.2).

[0015] In some embodiments, the ultrasound includes at least one of the following conditions:

[0016] (1) The ultrasound is performed in a water bath;

[0017] Optionally, the temperature of the water bath is 0°C-25°C;

[0018] (2) The ultrasonic time is 100 min-140 min, and the ultrasonic frequency is 28 kHz-40 kHz.

[0019] In some embodiments, the first calcination treatment includes at least one of the following conditions:

[0020] (1) The temperature of the first calcination treatment is 700° C.-900° C.;

[0021] (2) The first calcination treatment time is 2h-5h;

[0022] (3) the first calcination treatment is carried out in an inert atmosphere;

[0023] Optionally, the inert atmosphere comprises argon.

[0024] In some embodiments, the method for preparing the lithium cobalt oxide comprises:

[0025] A lithium source, a cobalt source and an M' source are mixed and subjected to a second calcination treatment to prepare the lithium cobalt oxide.

[0026] In some embodiments, the method for preparing the lithium cobalt oxide includes at least one of the following conditions:

[0027] (1) The lithium source includes one or more of lithium hydroxide, lithium nitrate, lithium carbonate, lithium oxalate, lithium fluoride, lithium bromide, lithium chloride, lithium acetate, lithium oxide, lithium citrate, lithium dihydrogen phosphate and lithium phosphate;

[0028] (2) the cobalt source comprises one or more of cobalt tetroxide, cobaltous oxide, cobalt trioxide, cobalt acetate, cobalt sulfate, cobalt nitrate, cobalt chloride, cobalt carbonate, cobalt oxalate, cobalt hydroxide and cobalt oxyhydroxide;

[0029] (3) The M' source includes an oxide containing an M' element;

[0030] Optionally, the M' element includes one or more combinations of Mg, Ti, Ni, Mn, W, Y, Mn, F, Zr, B, Al, V, Zn, Nb and La;

[0031] (4) The molar ratio of the lithium element contained in the lithium source to the cobalt element contained in the cobalt source is (1-1.2):1;

[0032] (5) The mass content of the M' element contained in the M' source relative to the mass content of the cobalt source is 500ppm-20000ppm;

[0033] (6) The temperature of the second calcination treatment is 700° C.-1100° C.;

[0034] (7) The calcination time is 3h-20h.

[0035] In some embodiments, the preparation method further comprises:

[0036] Crushing the material after the first calcination process;

[0037] Optionally, the crushing process takes 5 minutes to 10 minutes;

[0038] Optionally, the rotation speed of the high-speed crusher used in the crushing process is 1000rpm-9000rpm.

[0039] In some embodiments, the preparation method further comprises:

[0040] The material after the second calcination process is subjected to conventional mechanical crushing process.

[0041] The third aspect of the present invention provides a positive electrode plate, comprising the lithium cobalt oxide positive electrode material of the first aspect of the present invention or the lithium cobalt oxide positive electrode material prepared by the method of the second aspect of the present invention.

[0042] A fourth aspect of the present invention provides a secondary battery, comprising the positive electrode sheet according to the third aspect of the present invention.

[0043] A fifth aspect of the present invention provides an electrical device comprising the secondary battery according to the fourth aspect of the present invention.

[0044] The above-mentioned lithium cobalt oxide positive electrode material and its preparation method, positive electrode plate, secondary battery and power-consuming device, the coating layer of the lithium cobalt oxide positive electrode material contains a few layers of MXene material with high conductivity, which can maintain the structural stability of lithium cobalt oxide, improve the conductivity of the surface of lithium cobalt oxide, and provide higher ionic conductivity and electronic conductivity on the surface of lithium cobalt oxide particles, thereby driving more Li + The insertion / extraction of lithium cobalt oxide cathode materials can improve the electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 The cycle performance test results of Examples 1-6 and Comparative Example 1 are shown;

[0046] Figure 2 The conductivity test results of the lithium cobalt oxide positive electrode materials of Examples 1-6 and Comparative Example 1 are shown. DETAILED DESCRIPTION

[0047] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0048] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0049] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0050] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0051] Only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and likewise any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.

[0052] The temperature parameters in the present invention, if not specifically limited, allow for both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the precision range controlled by the instrument.

[0053] In the description of the invention, “plurality” means at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0054] If there is no special description, all embodiments and optional embodiments of the present invention can be combined with each other to form a new technical solution. If there is no special description, all technical features and optional technical features of the present invention can be combined with each other to form a new technical solution.

[0055] If not specifically stated, all steps of the present invention may be performed sequentially or randomly, but are preferably performed sequentially.

[0056] The few-layer MXene material mentioned in the present invention refers to a MXene material with a thickness of nanometer level (1nm-500nm).

[0057] Coating the surface of lithium cobalt oxide can reduce stress, increase the wettability of liquid electrolytes, reduce interfacial charge transfer resistance, and reduce side reactions, thereby effectively optimizing lithium cobalt oxide materials. However, since the coating layer is currently mostly coated with inert metal oxides, although the coating layer can effectively alleviate the violent reaction between lithium cobalt oxide and electrolyte, it also reduces the transmission rate of lithium ions, thereby affecting the electrochemical performance of the positive electrode material.

[0058] Based on the above problems, the present invention provides a lithium cobalt oxide positive electrode material and a preparation method thereof, wherein a few layers of MXene material are uniformly coated on the surface of lithium cobalt oxide in situ, and the few layers of MXene material are subjected to high temperature annealing treatment under an inert gas to prepare a lithium cobalt oxide positive electrode material coated with a few layers of MXene. The high conductivity of the few layers of MXene material is utilized to maintain the stability of the lithium cobalt oxide structure, improve the conductivity of the lithium cobalt oxide surface, and provide higher ionic conductivity and electronic conductivity on the surface of the lithium cobalt oxide particles, thereby improving the electrochemical performance of the lithium cobalt oxide positive electrode material.

[0059] The first aspect of the present invention provides a lithium cobalt oxide positive electrode material, comprising a core and a coating layer coated on at least a portion of the surface of the core; the core comprises lithium cobalt oxide doped with a metal element or a non-metal element, and the coating layer comprises a chemical formula of M n+1 X n A few-layer MXene material, wherein the M element includes one or more of Ta, Ti, V, Cr, Zr, Nb and Mo, the X element includes one or more of C and N, the surface end groups of the few-layer MXene material include one or more of -O, -OH and -F, n is a positive integer, and 1≤n≤3.

[0060] It should be noted that few-layer MXene materials refer to two-dimensional transition metal carbides, nitrides or carbonitrides.

[0061] The coating layer may be coated on only part of the surface of the core, or may be coated on the entire surface of the core.

[0062] Understandably, the coating layer of the lithium cobalt oxide positive electrode material contains a few layers of MXene material with high conductivity, which can maintain the structural stability of lithium cobalt oxide, improve the conductivity of the surface of lithium cobalt oxide, and provide higher ionic and electronic conductivity on the surface of lithium cobalt oxide particles, thereby driving more Li + The insertion / extraction of lithium cobalt oxide cathode materials can improve the electrochemical performance.

[0063] Few-layer MXene materials can increase the catalytic decomposition energy barrier of LiPF6 and organic electrolytes at the interface of lithium cobalt oxide positive electrode materials, thereby reducing the decomposition of LiPF6 and organic electrolytes and preventing the increase in interfacial impedance due to excessive accumulation of the positive electrode electrolyte interface film (CEI film) at the interface; Few-layer MXene materials can also reduce the corrosion of electrolyte on lithium cobalt oxide by inhibiting the decomposition of LiPF6, thereby preventing damage to the structure from the outside to the inside.

[0064] Compared with uncoated lithium cobalt oxide materials, after lithium cobalt oxide is coated with a few layers of MXene material, a stable CEI film can be formed at the interface between the positive electrode and the electrolyte during the battery charging and discharging process, thereby reducing the interfacial impedance and providing high capacity.

[0065] In some embodiments, the chemical formula of lithium cobalt oxide is Li a Co b M' c O2, wherein 0.97≤a≤1.02, 0.8≤b≤1.02, 0.002≤c≤0.05, and the M' element includes a combination of one or more of Mg, Ti, Ni, Mn, W, Y, Mn, F, Zr, B, Al, V, Zn, Nb and La.

[0066] In some possible embodiments, the thickness of the coating layer is 5nm-30nm; for example, it can be but is not limited to 5nm, 7nm, 10nm, 13nm, 15nm, 17nm, 20nm, 23nm, 25nm, 27nm, 30nm or a thickness range between any two of the above thicknesses.

[0067] The second aspect of the present invention provides a method for preparing the lithium cobalt oxide positive electrode material of the first aspect, comprising the following steps:

[0068] The lithium cobalt oxide is mixed with a solvent, ultrasonicated, and a few-layer MXene material is added to prepare a dispersion;

[0069] After removing the solvent from the dispersion, a first calcination treatment is performed to prepare a lithium cobalt oxide positive electrode material.

[0070] It should be noted that the "first calcination treatment" mentioned above is for descriptive purposes only and cannot be understood as indicating or implying relative importance or quantity, nor can it be understood as implicitly indicating the importance or quantity of the indicated technical features.

[0071] It can be understood that during the preparation process, the first calcination treatment can change the end groups of the few-layer MXene material and remove some end groups with poor stability, thereby improving the surface stability of the few-layer MXene material and enhancing the overall electrochemical performance of the lithium cobalt oxide positive electrode material.

[0072] In some embodiments, the solvent is water.

[0073] As a possible implementation, the mass ratio of lithium cobalt oxide to the few-layer MXene material is 10:(0.05-0.2); for example, it can be but not limited to 10:0.05, 10:0.06, 10:0.07, 10:0.08, 10:0.09, 10:0.1, 10:0.11, 10:0.12, 10:0.13, 10:0.14, 10:0.15, 10:0.16, 10:0.17, 10:0.18, 10:0.19, 10:0.2 or a range between any two of the above values. When the mass ratio of lithium cobalt oxide to the few-layer MXene material is within the above range, the thickness of the few-layer MXene coating layer is moderate and has a better coating effect.

[0074] In some embodiments, ultrasound is performed in a water bath; optionally, the temperature of the water bath is 0°C-25°C; for example, it can be but is not limited to 0°C, 3°C, 5°C, 8°C, 10°C, 12°C, 15°C, 18°C, 20°C, 23°C, 25°C or a temperature range between any two of the above temperatures.

[0075] In some embodiments, the ultrasonic time is 100 min-140 min; for example, it can be but not limited to 100 min, 105 min, 110 min, 115 min, 120 min, 125 min, 130 min, 135 min, 140 min or a range between any two of the above values. When the ultrasonic time is controlled within the above range, the ultrasonic dispersion is in a uniform state; when the ultrasonic time is less than the above range, the ultrasonic dispersion is uneven; when the ultrasonic time is greater than the range, the surface layer of the cobalt lithium oxide will be destroyed by high-frequency ultrasound.

[0076] The frequency of ultrasound is 28kHz-40kHz; for example, it can be but not limited to 28kHz, 29kHz, 30kHz, 31kHz, 32kHz, 33kHz, 34kHz, 35kHz, 36kHz, 37kHz, 38kHz, 39kHz, 40kHz or a frequency range between any two of the above frequencies.

[0077] As a possible embodiment, the temperature of the first calcination treatment is 700°C-900°C; for example, it can be but not limited to 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C, 900°C or the range between any two of the above values. When the temperature of the first calcination treatment is within the above range, the oxygen-containing groups can fully react; when the temperature of the first calcination treatment is lower than the above range, some oxygen-containing groups may not react completely; when the temperature of the first calcination treatment is higher than the above range, the reaction will be violent, which may cause excessive oxides to be generated on the surface to affect the conductivity.

[0078] In some optional embodiments, the time of the first calcination treatment is 2h-5h; for example, it can be but is not limited to 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h or a range between any two of the above values.

[0079] In some optional embodiments, the first calcination treatment is performed in an inert atmosphere; optionally, the inert atmosphere includes argon.

[0080] In some embodiments, the method for preparing lithium cobalt oxide comprises:

[0081] The lithium source, the cobalt source and the M' source are mixed and subjected to a second calcination treatment to prepare lithium cobalt oxide.

[0082] It should be noted that the "second calcination treatment" mentioned above is for descriptive purposes only and cannot be understood as indicating or implying relative importance or quantity, nor can it be understood as implicitly indicating the importance or quantity of the indicated technical features.

[0083] In some optional embodiments, the lithium source includes one or more of lithium hydroxide, lithium nitrate, lithium carbonate, lithium oxalate, lithium fluoride, lithium bromide, lithium chloride, lithium acetate, lithium oxide, lithium citrate, lithium dihydrogen phosphate and lithium phosphate.

[0084] In some optional embodiments, the cobalt source includes one or more of cobalt tetroxide, cobaltous oxide, cobalt trioxide, cobalt acetate, cobalt sulfate, cobalt nitrate, cobalt chloride, cobalt carbonate, cobalt oxalate, cobalt hydroxide and cobalt oxyhydroxide.

[0085] In some optional embodiments, the M' source includes an oxide containing the M' element; optionally, the M' element includes a combination of one or more of Mg, Ti, Ni, Mn, W, Y, Mn, F, Zr, B, Al, V, Zn, Nb and La.

[0086] In some optional embodiments, the molar ratio of the lithium element contained in the lithium source to the cobalt element contained in the cobalt source is (1-1.2):1; for example, it can be but is not limited to 1:1, 1.01:1, 1.02:1, 1.03:1, 1.04:1, 1.05:1, 1.06:1, 1.07:1, 1.08:1, 1.09:1, 1.1:1, 1.11:1, 1.12:1, 1.13:1, 1.14:1, 1.15:1, 1.16:1, 1.17:1, 1.18:1, 1.19:1, 1.2:1 or a range between any two of the above ratios.

[0087] In some optional embodiments, the mass content of the M' element contained in the M' source relative to the mass content of the cobalt source is 500ppm-20000ppm; for example, it can be 500ppm, 1000ppm, 2000ppm, 3000ppm, 4000ppm, 5000ppm, 6000ppm, 7000ppm, 8000ppm, 9000ppm, 10000ppm, 11000ppm, 12000ppm, 13000ppm, 14000ppm, 15000ppm, 16000ppm, 17000ppm, 18000ppm, 19000ppm, 20000ppm or a range between any two of the above values.

[0088] In some optional embodiments, the temperature of the second calcination treatment is 700°C-1100°C; for example, it can be but not limited to 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C or a range between any two of the above values.

[0089] In some optional embodiments, the time of the second calcination treatment is 3h-20h; for example, it can be but is not limited to 3h, 5h, 8h, 10h, 13h, 15h, 17h, 20h or a range between any two of the above values.

[0090] As a possible implementation manner, the method for preparing a lithium cobalt oxide positive electrode material further includes: crushing the material after the first calcination treatment.

[0091] In some optional embodiments, the crushing treatment time is 5 min-10 min; for example, it can be but is not limited to 5 min, 6 min, 7 min, 8 min, 9 min, 10 min or a range between any two of the above values.

[0092] In some optional embodiments, the rotation speed of the crusher used in the crushing process is 1000rpm-9000rpm; for example, it can be but not limited to 1000rpm, 2000rpm, 3000rpm, 4000rpm, 5000rpm, 6000rpm, 7000rpm, 8000rpm, 9000rpm or a range between any two of the above values.

[0093] In some embodiments, the dispersion is stirred at 40° C. to 60° C. until the solvent in the dispersion is removed.

[0094] The third aspect of the present invention provides a positive electrode plate, comprising the lithium cobalt oxide positive electrode material of the first aspect or the lithium cobalt oxide positive electrode material prepared by the method of the second aspect.

[0095] The fourth aspect of the present invention provides a secondary battery, comprising the positive electrode sheet of the third aspect of the present invention. The secondary battery of the present invention comprises the above-mentioned lithium cobalt oxide positive electrode material and has excellent electrochemical performance.

[0096] A fifth aspect of the present invention provides an electrical device including the secondary battery of the fifth aspect of the present invention.

[0097] The technical solution of the present invention is described in detail below in conjunction with specific embodiments.

[0098] 1. Preparation of positive electrode materials

[0099] It should be noted that the surface end groups of the few-layer MXene materials used in the following embodiments all include -O, -OH and -F.

[0100] Example 1

[0101] 146 g of lithium carbonate (as a lithium source), 300 g of cobalt tetroxide (as a cobalt source), magnesium oxide (as an M source), and aluminum oxide (as an M source) were mixed evenly, and heated at 800 ° C for 3.5 h, and then the temperature was increased to 1090 ° C for 5 hours, and naturally cooled to room temperature, crushed, and sieved to obtain lithium cobalt oxide LiCo 0.98 Mg 0.005 Al 0.015 O2; wherein the mass content of magnesium contained in magnesium oxide relative to the mass content of the cobalt source is 1200ppm, and the mass content of aluminum contained in aluminum oxide relative to the mass content of the cobalt source is 9000ppm.

[0102] 10g LiCo 0.98 Mg 0.005 Al 0.015O2 was added into deionized water and ultrasonically dispersed for 130 minutes, and the ultrasound was carried out in a water bath below 25°C; 0.05g Ti3C2 (a few-layer MXene material containing end groups) was added into the solution, and stirring was continued at a constant temperature of 50°C until the water in the solution completely evaporated and disappeared, then the powder was taken out and sintered in an argon atmosphere at 720°C for 5 hours. The powder was crushed and pulverized at 8000rpm for 5 minutes using a high-speed rotating equipment to obtain a few-layer MXene-coated lithium cobalt oxide positive electrode material.

[0103] Example 2

[0104] 146 g of lithium carbonate (as a lithium source), 300 g of cobalt tetroxide (as a cobalt source), magnesium oxide (as an M source), and aluminum oxide (as an M source) were mixed evenly, and heated at 800 ° C for 4 h, and then the temperature was increased to 1090 ° C for 5 hours, and naturally cooled to room temperature, crushed, and sieved to obtain lithium cobalt oxide LiCo 0.98 Mg 0.005 Al 0.015 O2; wherein the mass content of magnesium contained in magnesium oxide relative to the mass content of the cobalt source is 1200ppm, and the mass content of aluminum contained in aluminum oxide relative to the mass content of the cobalt source is 9000ppm.

[0105] 10g LiCo 0.98 Mg 0.004 Al 0.016 O2 was added into deionized water and ultrasonically dispersed for 130 minutes, and the ultrasound was carried out in a water bath below 25°C; 0.1g Ti3C2 (a few-layer MXene material containing end groups) was added into the solution, and stirring was continued at a constant temperature of 50°C until the water in the solution completely evaporated and disappeared, then the powder was taken out, sintered in an argon atmosphere at 720°C for 5 hours, and then the powder was crushed and pulverized at 8000rpm for 5 minutes using a high-speed rotating equipment to obtain a few-layer MXene-coated lithium cobalt oxide positive electrode material.

[0106] Example 3

[0107] 146 g of lithium carbonate (as a lithium source), 300 g of cobalt tetroxide (as a cobalt source), magnesium oxide (as an M source), and aluminum oxide (as an M source) were mixed evenly, and heated at 800 ° C for 4 h, and then the temperature was increased to 1090 ° C for 5 hours, and naturally cooled to room temperature, crushed, and sieved to obtain lithium cobalt oxide LiCo 0.98 Mg 0.005 Al 0.015 O2; wherein the mass content of magnesium contained in magnesium oxide relative to the mass content of the cobalt source is 1200ppm, and the mass content of aluminum contained in aluminum oxide relative to the mass content of the cobalt source is 9000ppm.

[0108] 10g LiCo 0.98 Mg 0.005 Al 0.015 O2 was added into deionized water and ultrasonically dispersed for 120 minutes, and the ultrasound was carried out in a water bath below 25°C; 0.2g Ti3C2 (a few-layer MXene material containing end groups) was added into the solution, and stirring was continued at a constant temperature of 50°C until the water in the solution completely evaporated and disappeared, then the powder was taken out and sintered in an argon atmosphere at 850°C for 2.5 hours. The powder was crushed and pulverized at 5000rpm for 8 minutes using a high-speed rotating equipment to obtain a few-layer MXene-coated lithium cobalt oxide positive electrode material.

[0109] Example 4

[0110] 146 g of lithium carbonate (as a lithium source), 300 g of cobalt tetroxide (as a cobalt source), magnesium oxide (as an M source), and aluminum oxide (as an M source) were mixed evenly, and heated at 800 ° C for 4 h, and then the temperature was increased to 1090 ° C for 5 hours, and naturally cooled to room temperature, crushed, and sieved to obtain lithium cobalt oxide LiCo 0.98 Mg 0.005 Al 0.015 O2; wherein the mass content of magnesium contained in magnesium oxide relative to the mass content of the cobalt source is 1200ppm, and the mass content of aluminum contained in aluminum oxide relative to the mass content of the cobalt source is 9000ppm.

[0111] 10g LiCo 0.98 Mg 0.005 Al 0.015 O2 was added into deionized water and ultrasonically dispersed for 110 minutes, and the ultrasound was carried out in a water bath below 25°C; 0.1g Zr3C2 (a few-layer MXene material containing end groups) was added into the solution, and stirring was continued at a constant temperature of 50°C until the water in the solution completely evaporated and disappeared, then the powder was taken out, sintered in an argon atmosphere at 800°C for 3 hours, and then the powder was crushed and pulverized at 4000rpm for 8 minutes using a high-speed rotating equipment to obtain a few-layer MXene-coated lithium cobalt oxide positive electrode material.

[0112] Example 5

[0113] 146 g of lithium carbonate (as a lithium source), 300 g of cobalt tetroxide (as a cobalt source), magnesium oxide (as an M source), and aluminum oxide (as an M source) were mixed evenly, and heated at 800 ° C for 3.5 h, and then the temperature was increased to 1090 ° C for 5 hours, and naturally cooled to room temperature, crushed, and sieved to obtain lithium cobalt oxide LiCo 0.98 Mg 0.005 Al 0.015O2; wherein the mass content of magnesium contained in magnesium oxide relative to the mass content of the cobalt source is 1200ppm, and the mass content of aluminum contained in aluminum oxide relative to the mass content of the cobalt source is 9000ppm.

[0114] 10g LiCo 0.98 Mg 0.005 Al 0.015 O2 was added into deionized water and ultrasonically dispersed for 130 minutes, and the ultrasound was carried out in a water bath below 25°C; 0.1g Ti2N (a few-layer MXene material containing end groups) was added into the solution, and stirring was continued at a constant temperature of 50°C until the water in the solution completely evaporated and disappeared, and then the powder was taken out, sintered in an argon atmosphere at 720°C for 5 hours, and then the powder was crushed and pulverized at 8000rpm for 5 minutes using a high-speed rotating equipment to obtain a few-layer MXene-coated lithium cobalt oxide positive electrode material.

[0115] Example 6

[0116] 146 g of lithium carbonate (as a lithium source), 300 g of cobalt tetroxide (as a cobalt source), magnesium oxide (as an M source), and aluminum oxide (as an M source) were mixed evenly, and heated at 800 ° C for 3.5 h, and then the temperature was increased to 1090 ° C for 5 hours, and naturally cooled to room temperature, crushed, and sieved to obtain lithium cobalt oxide LiCo 0.98 Mg 0.005 Al 0.015 O2; wherein the mass content of magnesium contained in magnesium oxide relative to the mass content of the cobalt source is 1200ppm, and the mass content of aluminum contained in aluminum oxide relative to the mass content of the cobalt source is 9000ppm.

[0117] 10g LiCo 0.98 Mg 0.005 Al 0.015 O2 was added into deionized water and ultrasonically dispersed for 130 minutes, and the ultrasound was carried out in a water bath below 25°C; 0.1g Nb2C (a few-layer MXene material containing end groups) was added into the solution, and stirring was continued at a constant temperature of 50°C until the water in the solution completely evaporated and disappeared, and then the powder was taken out, sintered in an argon atmosphere at 720°C for 5 hours, and then the powder was crushed and pulverized at 8000rpm for 5 minutes using a high-speed rotating equipment to obtain a few-layer MXene-coated lithium cobalt oxide positive electrode material.

[0118] Comparative Example 1

[0119] The difference between the lithium cobalt oxide positive electrode material in Comparative Example 1 and the lithium cobalt oxide positive electrode material in Example 1 is that the MXene material is not coated. The specific preparation process is as follows:

[0120] 146 g of lithium carbonate (as a lithium source), 300 g of cobalt tetroxide (as a cobalt source), magnesium oxide (as an M source), and aluminum oxide (as an M source) were mixed evenly, and heated at 800 ° C for 3.5 h, and then the temperature was increased to 1090 ° C for 5 hours, and naturally cooled to room temperature, crushed, and sieved to obtain lithium cobalt oxide LiCo 0.98 Mg 0.005 Al 0.015 O2; wherein the mass content of magnesium contained in magnesium oxide relative to the mass content of the cobalt source is 1200ppm, and the mass content of aluminum contained in aluminum oxide relative to the mass content of the cobalt source is 9000ppm.

[0121] Comparative Example 2

[0122] 146 g of lithium carbonate (as a lithium source), 300 g of cobalt tetroxide (as a cobalt source), magnesium oxide (as an M source), and aluminum oxide (as an M source) were mixed evenly, and heated at 800 ° C for 3.5 h, and then the temperature was increased to 1090 ° C for 5 hours, and naturally cooled to room temperature, crushed, and sieved to obtain lithium cobalt oxide LiCo 0.98 Mg 0.005 Al 0.015 O2; wherein the mass content of magnesium contained in magnesium oxide relative to the mass content of the cobalt source is 1200ppm, and the mass content of aluminum contained in aluminum oxide relative to the mass content of the cobalt source is 9000ppm.

[0123] 10g LiCo 0.98 Mg 0.005 Al 0.015 O2 was added into deionized water and ultrasonically dispersed for 130 minutes, and the ultrasound was carried out in a water bath below 25°C; 0.05g Ti3C2 (multilayer MXene material containing end groups, the thickness of the multilayer MXene material was 1-20μm) was added into the solution, and stirring was continued at a constant temperature of 50°C until the water in the solution completely evaporated and disappeared, then the powder was taken out, sintered in an argon atmosphere at 720°C for 5h, and then the powder was crushed and pulverized at 8000rpm for 5min using a high-speed rotating equipment to obtain a multilayer MXene-coated lithium cobalt oxide positive electrode material.

[0124] Comparative Example 3

[0125] 146 g of lithium carbonate (as a lithium source), 300 g of cobalt tetroxide (as a cobalt source), magnesium oxide (as an M source), and aluminum oxide (as an M source) were mixed evenly, and heated at 800 ° C for 3.5 h, and then the temperature was increased to 1090 ° C for 5 hours, and naturally cooled to room temperature, crushed, and sieved to obtain lithium cobalt oxide LiCo 0.98 Mg 0.005 Al 0.015O2; wherein the mass content of magnesium contained in magnesium oxide relative to the mass content of the cobalt source is 1200ppm, and the mass content of aluminum contained in aluminum oxide relative to the mass content of the cobalt source is 9000ppm.

[0126] 10g LiCo 0.98 Mg 0.005 Al 0.015 O2 was added to deionized water and ultrasonically dispersed for 130 minutes, and the ultrasonication was carried out in a water bath below 25°C; 0.1g Al2O3 was added to the solution, and stirring was continued at a constant temperature of 50°C until the water in the solution completely evaporated and disappeared, and then the powder was taken out, sintered in an argon atmosphere at 720°C for 5 hours, and then the powder was crushed and pulverized using a high-speed rotating device at 8000rpm for 5 minutes to obtain Al-coated lithium cobalt oxide positive electrode materials. 2. Preparation of batteries

[0127] 1. Preparation of lithium ion electrode materials: The lithium cobalt oxide positive electrode materials prepared in the above embodiments and comparative examples were respectively mixed with conductive carbon black (as a conductive agent) and polyvinylidene fluoride (PVDF, as a binder) in a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) was added to make a slurry, which was then evenly coated on the surface of an aluminum foil. After vacuum drying at 120°C for 10 hours, the dried aluminum foil was punched into a circular electrode piece.

[0128] 2. Preparation of lithium-ion batteries: Pure lithium was used as the negative electrode, and the lithium cobalt oxide positive electrode material pole pieces prepared in the above embodiments and comparative examples were used as the positive electrode to assemble button batteries in a glove box filled with argon (O2<0.00001%, H2O<0.00001%).

[0129] 3. Performance Test

[0130] The LAND battery test system is used to perform constant current charge and discharge tests, high temperature cycle tests and conductivity tests on the assembled button batteries. The test methods are as follows:

[0131] 1. Constant current charge and discharge test: 1) Constant current charge: charging current is 0.1C, cut-off voltage is 4.55Vvs.Li / Li + ; 2) Constant voltage charging: charging voltage is 4.55V vs.Li / Li + , cut-off current is 0.05C; 3) Stand for 5 minutes; 4) Constant current discharge: discharge current is 0.1C, cut-off voltage is 3.0V vs.Li / Li + ; 5) let stand for 5 min. The constant current charge and discharge tests of the above embodiments and comparative examples are shown in Table 1.

[0132] 2.45℃ high temperature cycle test: 1) Constant current charging: charging current is 1C, cut-off voltage is 4.55Vvs.Li / Li+ , cut-off current is 0.05C; 2) Stand for 5 minutes; 3) Constant current discharge: discharge current is 1C, cut-off voltage is 3.0V vs.Li / Li + ; 4) let stand for 5 minutes, repeat 1-4 cycles for 50 cycles. The high temperature cycle test results of the above embodiments and comparative examples are shown in Table 1. The cycle performance test curves of embodiments 1-6 and comparative example 1 are shown in Table 1. Figure 1 shown.

[0133] 3. Conductivity test

[0134] The conductivity of lithium cobalt oxide powder was tested using PRCD1100 (IEST-Yuan Neng Technology). The test parameters were as follows: applied pressure range 10-200 MPa, pressurization interval 10 MPa, pressure holding 10 s, pressure relief to 3 MPa, pressure holding 10 s. The conductivity test results of Examples 1-6 and Comparative Example 1 are shown in Figure 2. Figure 2 shown.

[0135] Table 1

[0136]

[0137] From the comparison of the results of Examples 1-6 and Comparative Examples 1-3 in Table 1, it can be seen that compared with not using a few-layer MXene material to coat lithium cobalt oxide, and using a multi-layer MXene material or an inert oxide to coat lithium cobalt oxide, the charge and discharge capacity, first coulomb efficiency and cycle capacity retention rate of the lithium cobalt oxide positive electrode material obtained by coating lithium cobalt oxide with a few-layer MXene material are increased, among which when the few-layer MXene material is 1% of the amount of lithium cobalt oxide, the coating effect is better.

[0138] Depend on Figure 2 It can be seen that using a few layers of MXene material to coat lithium cobalt oxide can significantly improve the conductivity of lithium cobalt oxide, thereby accelerating the insertion and extraction of lithium ions, and thus increasing the capacity.

[0139] Depend on Figure 1 It can be seen that the cycle performance of the lithium cobalt oxide positive electrode material obtained by coating lithium cobalt oxide with a few layers of MXene material is significantly improved, indicating that the coating layer protects the lithium cobalt oxide and reduces the decomposition of the electrolyte on the positive electrode surface, thereby improving the cycle performance.

[0140] In summary, the coating layer of the present invention improves the electrochemical performance of the lithium cobalt oxide positive electrode material.

[0141] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0142] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A lithium cobalt oxide positive electrode material, characterized in that: include: A core, the core comprising lithium cobalt oxide doped with a metal element or a non-metal element; and The coating layer is coated on at least part of the surface of the core, and the coating layer comprises a chemical formula of M n+1 X n A few-layer MXene material, wherein the M element includes one or more of Ta, Ti, V, Cr, Zr, Nb and Mo, the X element includes one or more of C and N, the surface end groups of the few-layer MXene material include one or more of -O, -OH and -F, n is a positive integer, and 1≤n≤3.

2. The lithium cobalt oxide positive electrode material according to claim 1, characterized in that: The chemical formula of the lithium cobalt oxide is Li a Co b M' c O2, wherein 0.97≤a≤1.02, 0.8≤b≤1.02, 0.002≤c≤0.05, and the M' element includes a combination of one or more of Mg, Ti, Ni, Mn, W, Y, Mn, F, Zr, B, Al, V, Zn, Nb and La.

3. The lithium cobalt oxide positive electrode material according to any one of claims 1 to 2, characterized in that: The coating layer has a thickness of 5nm-30nm.

4. A method for preparing a lithium cobalt oxide positive electrode material according to any one of claims 1 to 3, characterized in that: The steps include: The lithium cobalt oxide is mixed with a solvent, ultrasonicated, and the few-layer MXene material is added to prepare a dispersion; The solvent in the dispersion is removed and then a first calcination treatment is performed to prepare the lithium cobalt oxide positive electrode material.

5. The method for preparing a lithium cobalt oxide positive electrode material according to claim 4, characterized in that: The mass ratio of the lithium cobalt oxide to the few-layer MXene material is 10:(0.05-0.2).

6. The method for preparing a lithium cobalt oxide positive electrode material according to claim 4, characterized in that: The ultrasound includes at least one of the following conditions: (1) The ultrasound is performed in a water bath; Optionally, the temperature of the water bath is 0°C-25°C; (2) The ultrasound duration is 100 min-140 min, and the ultrasound frequency is 28 kHz-40 kHz.

7. The method for preparing a lithium cobalt oxide positive electrode material according to claim 4, characterized in that: The first calcination treatment includes at least one of the following conditions: (1) The temperature of the first calcination treatment is 700° C.-900° C.; (2) The first calcination treatment time is 2h-5h; (3) the first calcination treatment is carried out in an inert atmosphere; Optionally, the inert atmosphere comprises argon.

8. The method for preparing a lithium cobalt oxide positive electrode material according to any one of claims 4 to 7, characterized in that: The preparation method of the lithium cobalt oxide comprises: A lithium source, a cobalt source and an M' source are mixed and subjected to a second calcination treatment to prepare the lithium cobalt oxide.

9. The method for preparing a lithium cobalt oxide positive electrode material according to claim 8, characterized in that: The preparation method of the lithium cobalt oxide includes at least one of the following conditions: (1) The lithium source includes one or more of lithium hydroxide, lithium nitrate, lithium carbonate, lithium oxalate, lithium fluoride, lithium bromide, lithium chloride, lithium acetate, lithium oxide, lithium citrate, lithium dihydrogen phosphate and lithium phosphate; (2) the cobalt source comprises one or more of cobalt tetroxide, cobaltous oxide, cobalt trioxide, cobalt acetate, cobalt sulfate, cobalt nitrate, cobalt chloride, cobalt carbonate, cobalt oxalate, cobalt hydroxide and cobalt oxyhydroxide; (3) The M' source includes an oxide containing an M' element; Optionally, the M' element includes one or more combinations of Mg, Ti, Ni, Mn, W, Y, Mn, F, Zr, B, Al, V, Zn, Nb and La; (4) The molar ratio of the lithium element contained in the lithium source to the cobalt element contained in the cobalt source is (1-1.2):1; (5) The mass content of the M' element contained in the M' source relative to the mass content of the cobalt source is 500ppm-20000ppm; (6) The temperature of the second calcination treatment is 700° C.-1100° C.; (7) The second calcination treatment time is 3h-20h.

10. The method for preparing a lithium cobalt oxide positive electrode material according to any one of claims 4 to 7, characterized in that: The preparation method further comprises: Crushing the material after the first calcination process; Optionally, the crushing process takes 5 minutes to 10 minutes; Optionally, the rotation speed of the high-speed crusher used in the crushing process is 1000rpm-9000rpm.

11. A positive electrode sheet, characterized in that: The invention comprises the lithium cobalt oxide positive electrode material according to any one of claims 1 to 3 or the lithium cobalt oxide positive electrode material prepared by the method according to any one of claims 4 to 10.

12. A secondary battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 11.

13. An electrical device, characterized in that: Comprising the secondary battery as claimed in claim 12.